1991
DOI: 10.1152/jappl.1991.70.2.631
|View full text |Cite
|
Sign up to set email alerts
|

Strength and skeletal muscle adaptations in heavy-resistance-trained women after detraining and retraining

Abstract: Six women who had participated in a previous 20-wk strength training study for the lower limb detrained for 30-32 wk and subsequently retrained for 6 wk. Seven untrained women also participated in the 6-wk "retraining" phase. In addition, four women from each group volunteered to continue training an additional 7 wk. The initial 20-wk training program caused an increase in maximal dynamic strength, hypertrophy of all three major fiber types, and a decrease in the percentage of type IIb fibers. Detraining had r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
233
3
17

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(267 citation statements)
references
References 0 publications
14
233
3
17
Order By: Relevance
“…muscle memory | muscle nuclei | muscle atrophy | muscle hypertrophy | apoptosis I ndividuals with a history of previous training acquire force quickly on retraining (1,2), and this commonly observed phenomenon has been dubbed "muscle memory." There is no known mechanism for memory in muscle cells, and, to date, the longlasting effects of previous training have been attributed to motor learning in the central nervous system (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…muscle memory | muscle nuclei | muscle atrophy | muscle hypertrophy | apoptosis I ndividuals with a history of previous training acquire force quickly on retraining (1,2), and this commonly observed phenomenon has been dubbed "muscle memory." There is no known mechanism for memory in muscle cells, and, to date, the longlasting effects of previous training have been attributed to motor learning in the central nervous system (3).…”
mentioning
confidence: 99%
“…There is no known mechanism for memory in muscle cells, and, to date, the longlasting effects of previous training have been attributed to motor learning in the central nervous system (3). However, it has been reported that muscles can remain hypertrophic after several months of detraining (1,(4)(5)(6)(7)(8). In one study on elderly individuals who had strength-trained, force was still 9-14% higher even after 2 y of detraining (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, resistance training-induced muscle anabolism and subsequent hypertrophy occur most rapidly during the early phases of training, becoming progressively slower with time (33,40). On the other hand, following a detraining period, muscle adaptation responses may return to their initial levels, and the effects of retraining on muscle growth are similar to those observed during the initial phase of resistance training (33,37). However, the mechanisms underlying such changes in the sensitivity of muscles to training stimuli are unclear.…”
mentioning
confidence: 99%
“…In fact, the retention of "surplus" nuclei during atrophy confers a distinct advantage for the individual since skeletal muscle frequently undergoes cycles of atrophy and hypertrophy in response to environmental conditions. The ability to recover quickly by utilizing pre-existing nuclei may serve an important role in muscle adaptation and may explain the phenomenon of "muscle memory" [54]. It is well documented in the field of exercise physiology that it is far easier to reacquire a certain level of muscle fitness through exercise then it was to achieve it the first place, even if there has been a long intervening period of detraining.…”
Section: Commentarymentioning
confidence: 99%